Impact of Strategic Management Practice on Marketing Strategies in Sudan telecommunication market - Abu Setah, Ali Abbas (Journal of Economic, Administrative and Legal Sciences, 2019)
The research aimed at testing the relationship between strategic management practice and marketing strategies, and to explore how could practicing strategic management effects on marketing strategies. The study is important as it is a try to contribute in completing the efforts of researchers who wanted to fill the gab concerned with source difference in performance. There is positive relationship between strategic management practice and marketing strategies. The research based on descriptive and analytical methodology. The data collected from its sources to build theoretical background in the research area. Statistical methods were used for descriptive and analytical description and analysis field study data and to test hypotheses. Data were collected by questionnaire distributed to a random sample represented employees in Sudan, telecommunication companies. The validity and the reliability of the study tool were verified by pilot study. The findings of the study showed that the companies are at primary steps of the strategic management practice and do not care about pricing. Also the study founded that strategic management practice affect positively on marketing strategies and its biggest effect on marketing communications while its less effect on product development and technology. The research recommended that the companies have to, exercise all steps of strategic management practice, take care for pricing, and concentrate more on product development and technology.